Prevalence of Porcine Circoviruses in Slaughterhouses in Central Shanxi Province, China - Yue, Weidong; Li, Yilei; Zhang, Xinrong; He, Junping; Ma, Haili (Frontiers in Veterinary Science, 2022)
Background: Porcine circovirus diseases is still the greatest threat to healthy pig farming, with four circovirus genotypes circulating worldwide. Objective: To better understand the prevalence of porcine circovirus genotypes in the central part of Shanxi Province . Methods: We investigated the prevalence porcine circovirus disease-causing pathogens including porcine circovirus type 2 (PCV2), porcine circovirus type 3 (PCV3), and porcine circovirus type 4 (PCV4). The pathogen of porcine circovirus was analyzed by polymerase chain reaction (PCR) in the lung tissues of 180 pigs from 7 slaughterhouses in central Shanxi Province, China . Results: The positive rates of PCV2, PCV3, and PCV4 in 56.77, 80.00, and 9.44% of the samples, respectively, and the negative rate of all four pathogens was 10.00%. The co-positive rates of PCV2 and PCV3, PCV2 and PCV4, PCV3 and PCV4, PCV2, PCV3 and PCV4 were 47.22, 7.41, 7.41, and 5.56, respectively. The PCV4-positive samples, the co-positive rates of PCV4 with PCV2 was 52.94% (9/17), and with PCV3 it was 100% (17/17). Conversely, PCV2 and PCV3 were detected in 57.06% (93/163) and 78.53% (128/163) of the samples, respectively in the PCV4-negative samples. Conclusions: The high positive rate of PCV3, the co-positive rate of PCV2 with PCV3,PCV3 with PCV4, suggestion seems to indicate that PCV3 plays a decisive role in PCV2 with PCV4 infection. Therefore, we should further need control measures to reduce the spread of the virus.